Implementation of Position Equalization in Civil Servant Management in the Bitung City Government - Dandel, Forsman F. T.; Sendouw, Recky; Bulo, Laurens (Technium Social Sciences Journal, 2025)
This study aims to analyze the implementation of position equalization in the Bitung City Government as part of the bureaucratic simplification efforts mandated by national regulations, especially Presidential Instruction Number 7 of 2019 and Regulation of the Minister of State Apparatus Empowerment and Bureaucratic Reform Number 17 of 2021. Equalization of positions that change echelon administrative positions into functional positions is expected to increase the professionalism of the state civil apparatus (ASN) and the effectiveness of public services. The research method uses a qualitative approach with data collection through interviews, observations, and document studies. The results showed that the process of equalizing positions in Bitung City was carried out gradually and selectively without a competency test in the early stages, as a form of adaptation to policy changes. Successful implementation was influenced by effective communication between work units, human resource competency development, and adequate organizational structure support. However, there are challenges related to competency gaps and uneven workload distribution that need to be addressed through systematic training and performance evaluation. This research confirms that position equalization in Bitung City has been running in accordance with modern bureaucratic management principles and applicable regulations, but the sustainability of the program’s success is highly dependent on planned competency development and regular monitoring. The findings provide important recommendations for other local governments that want to implement equalization in order to improve ASN professionalism and the quality of public services.